2015
DOI: 10.1515/nuka-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

First dedicated observations of runaway electrons in the COMPASS tokamak

Abstract: Abstract. Runaway electrons present an important part of the present efforts in nuclear fusion research with respect to the potential damage of the in-vessel components. The COMPASS tokamak a suitable tool for the studies of runaway electrons, due to its relatively low vacuum safety constraints, high experimental fl exibility and the possibility of reaching the H-mode D-shaped plasmas. In this work, results from the fi rst experimental COMPASS campaign dedicated to runaway electrons are presented and discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…In addition to the rise in , the normalised plasma pressure rises above for the same discharges and thus confirms that the overestimated as seen by EFIT (Vlainić et al. 2015) is caused by the presence of RE.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…In addition to the rise in , the normalised plasma pressure rises above for the same discharges and thus confirms that the overestimated as seen by EFIT (Vlainić et al. 2015) is caused by the presence of RE.…”
Section: Resultssupporting
confidence: 75%
“…After performing this calculation, it was observed that the l i value increases by a factor of 1.5-3.5, which is comparable to the measurements for JET (Loarte et al 2011). In addition to the rise in l i , the normalised plasma pressure β n rises above 1.5 for the same discharges and thus confirms that the overestimated β n as seen by EFIT (Vlainić et al 2015) is caused by the presence of RE.…”
Section: Resultssupporting
confidence: 72%
“…The pitch angle θ is taken to be 0.2 rad as a mean value found in Ref. [15]. The RE minor radius a RE for the RE area A RE calculation is assumed to be constant and equal to 5 cm.…”
Section: Result: Compass Discharge 7298mentioning
confidence: 99%
“…The very first magnetic observations of high RE current in the COMPASS tokamak are reported in Ref. [9] for discharge #7298. The discharge had circular-shaped limited plasma, with toroidal magnetic field B tor = 1.15 T and plasma current I p = 120 kA.…”
Section: Experiment: High Re Current Dischargementioning
confidence: 99%
See 1 more Smart Citation